Non-Linear behavior of Encryption Algorithm under windows Environment (Al-Mansour Journal, 2023)
This paper is devoted to present a new parameter that should be included along the design phase of and modular EA that will implemented on windows operating system. This parameter is the Tick Resolution (Tic) which represents how frequent the system will leave current process and give the control to other, this will be used to compromised EA and dig into integral black box. A mathematical model has been presented to formulate the relationship between Tic and the key parameters of EA which the complexity, this paper will prove the nonlinearity of the behavior of EA due to high tick resolution, where increasing the complexity might lead to worse security , an optimal solution has been proposed with other solutions. A practical test has been included to present the effectiveness of Tic on the EA linearity.